"Voluntarily, knowingly, and intelligently": - Jan Nadine DeFehr (Brock University, 2020)
Educators are part of in-school discussions about student mental health. At times, teachers may suggest that students consult with mental health professionals. Informed by mental health promotion resources, educator referrals to mental health professionals may lack discussion of critical mental health information. Mental health promotion materials do not acknowledge the extensive scholarly critique of mental health premises and practices. Much of this critique is produced within psychiatry, the disciplinary base of mental health. Critical scholarship discusses profound flaws, misinformation, and potential for harm within conventional mental health. Important critical mental health topics include scientific evidence, psychiatric drugs, and psychiatric diagnosis. Access to both critical and conventional mental health scholarship is necessary for students and parents to provide informed consent to mental health intervention. Some interventions commonly take place in the first meeting and therefore, students and parents need access to critical information prior to their first meeting with a mental health professional. Forming a critical mental health primer for teachers, this article goes beyond promotion of critical mental health awareness to call for institutional divestment from mental health premises and practices that cause harm and lack scientific, ethical, and intellectual integrity.